If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-22.8=x/6-3.6
We move all terms to the left:
-22.8-(x/6-3.6)=0
We get rid of parentheses
-x/6+3.6-22.8=0
We multiply all the terms by the denominator
-x+(3.6)*6-(22.8)*6=0
We add all the numbers together, and all the variables
-1x-115.2=0
We move all terms containing x to the left, all other terms to the right
-x=115.2
x=115.2/-1
x=-115+0.2/1
| 1/3(2x+6)=1/4(4x-3) | | 100-2x=20+6x | | 5p^2-10p-40=0 | | 32x-27=120 | | x^2+39=55 | | 9k−k=16 | | 9x+2+15x-52=180 | | 92-2x=20+6x | | 5-4k=-4k+10-7 | | 19x+2x+4x−8x−10x=14 | | 5.4d–2.3d+3(d–4)=16.67 | | 2y=42/5 | | 9x-10=5x | | (3x-5)=13 | | 16x-15x=13 | | 10x^2-20x-240=0 | | 3g-2g=17 | | 8x-13,2=6x-5,2 | | 19c-17c=18 | | 10=-6x+2(4x-4) | | 0x-0x=8 | | 5x+35/3=20 | | -19x-15=-110 | | y/2+8=10 | | x+4/5=8/5x+1/10 | | 6x+3=7-x | | 8y-(2y-3)=9y | | 14n-6n=8 | | 2x+20=3x-3(x-8) | | -.5x+3=-4 | | 4j+16=19 | | 4|4t-8|=80 |